Design of steel piles for integral abutment bridges - Petursson, Hans (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2015)
In 1999 research was started at Luleå University of Technology with the purpose to collect experiences from USA and UK on bridges with integral abutments and transfer the experience to Swedish conditions. Since then at least 20 integral bridges with one row of piles under each abutment have been built in Sweden and the European research project INTAB has been completed. Most of the bridges are short and it seems to be difficult to design integral bridges that are longer than 40 m. The reason for this being that piles in integral abutment bridges can experience severe strain during service due to soil restraint and annual fluctuations in bridge temperature, which displace and rotate the end of the pile that is clamped to the superstructure. Most design codes do not allow strains exceeding the yield point at the serviceability limit state (e.g. EN 1993-2). This will limit the possibility to build longer integral abutment bridges founded on steel piles. Since bridges are designed to be used 100 years or more, the strains caused by the annual temperature variations can be considered as a low cycle fatigue problem.The aim of this thesis is to improve the method to design steel piles in integral abutment bridges. This means that the designer with less effort should be able to make a safer or equally safe design as before by using the methods described in this thesis. The thesis describes how the analysis of piles of integral abutment bridges can be done. In order to study how steel piles in integral abutments are used and how they behave an international workshop was arranged in Stockholm (Collin et. al. 2006), a literature study was conducted, a bridge was designed, built and monitored and laboratory tests were made. With the results from the research activities as base a design method is suggested. Under 1999 startades ett forskningsprojekt vid Luleå tekniska universitet med syfte att samla in erfarenheter, vad gäller broar med integrerade landfästen, från USA och Storbritannien och överföra dessa till svenska ...